2016
DOI: 10.2741/4425
|View full text |Cite
|
Sign up to set email alerts
|

Nitro-fatty acids in cardiovascular regulation and diseases characteristics and molecular mechanisms

Abstract: Electrophilic nitro-fatty acids (NO2-FAs) are endogenously formed by redox reactions of nitric oxide (•NO)- and nitrite (•NO2)- derived nitrogen dioxide with unsaturated fatty acids. Nitration preferentially occurs on polyunsaturated fatty acids with conjugated dienes under physiological or pathophysiological conditions such as during digestion, metabolism and as adaptive inflammatory processes. Nitro-fatty acids are present in free and esterified forms achieving broad biodistribution in humans and experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 108 publications
(166 reference statements)
2
35
0
Order By: Relevance
“…Results obtained in animal systems have shown that nitroalkylation of specific anti-inflammatory and antioxidant-related proteins leads to the modification of their activities, thus promoting important beneficial mechanisms [2], [7]. Due to there is no information available concerning this PTM in plants, analyzing this capacity with key components of antioxidant pathways could be useful to understand the mechanism of action of NO 2 -FAs in plant systems.…”
Section: Signaling Role Of No2-ln In Plant Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Results obtained in animal systems have shown that nitroalkylation of specific anti-inflammatory and antioxidant-related proteins leads to the modification of their activities, thus promoting important beneficial mechanisms [2], [7]. Due to there is no information available concerning this PTM in plants, analyzing this capacity with key components of antioxidant pathways could be useful to understand the mechanism of action of NO 2 -FAs in plant systems.…”
Section: Signaling Role Of No2-ln In Plant Physiologymentioning
confidence: 99%
“…Numerous studies have since reported a selective nitration of fatty acids under physiological conditions, highlighting the greater susceptibility to nitration of conjugated fatty acids than methyl-interrupted dienes or polyenes in animal systems [5]. Most of these analyses have shown that these molecules trigger pleiotropic signaling actions including a remarkable anti-inflammatory and antioxidant response [6], [7], [8], [9]. A measurable increase in the levels of NO 2 -FAs has been shown under different pathological conditions such as ischemia reperfusion injury or after LPS injection in the peritoneum [1], [10].…”
Section: Introductionmentioning
confidence: 99%
“…These NO 2 and N 2 O 3 -generating reactions are also likely to produce nitro-fatty acids (14,154,193,194) in the RBC membrane. Nitro-fatty acid derivatives of oleic acid have been found in RBC membranes (15).…”
Section: Preserving Transporting and Delivering Hb-derived Nox Bioamentioning
confidence: 99%
“…Production of the NO 2 radical at a moderate rate is likely to be anti-inflammatory, in that it can both regenerate free NO by oxidizing HbNO to form met Hb plus NO (20) and help generate nitro-fatty acids, which have impressive antiinflammatory properties (8,58,194). NO 2 is also produced via the complex reaction of nitrite with oxyHb in a reaction that involves ferryl formation (77,91,135).…”
Section: The Interplay Of Reduced Nox Generation and Enhanced Ferryl mentioning
confidence: 99%
“…[7] Nitro-fatty acids (NO 2 -FA) have been found both in vitro and in vivo, namely in red blood cells, [8,9] plasma, [8][9][10][11] and in different tissues, either in normal or in inflammatory conditions. [12] Several published works described the NO 2 -FA adducts with GSH, [13,14] GAPDH, [13,14] NF-κB, [15] and PPARγ. [16] This type of post-translational modification seems to be an important regulatory pathway for the modulation of enzymatic activity, redox homeostasis, and in signaling events [7,13,17] associated with inhibition of inflammatory process and pro-survival responses.…”
Section: Introductionmentioning
confidence: 99%